ANALISIS SENSITIVITAS LINGKUNGAN OSCP (OIL SPILL CONTINGENCY PLAN) DI PESISIR SELATAN DELTA MAHAKAM, PROVINSI KALIMANTAN TIMUR - Mursalin Mursalin; I Wayan Nurjaya; Hefni Effendi (Graduate School Bogor Agricultural University (SPs IPB), 2014)
The research was one part of oil spill contingency plan (OSCP) developed for Delta Mahakam area, where oil & gas exploration and exploitation linked with rich biodiversity supporting coastal community livelihood. Environmental sensitivity analysis for OSCP only do two early stages of OSCP scope, which integrated with the dangers of coastal vulnerability. This analysis mapped environmental component from oil pollution become sensitivity rangking as an effort to support response development strategies and priorities for the coastal resources protection. The aims of this research were (1) to establish environment sensitivity rank and (2) to identify primary factor supporting the environmental sensitivity for OSCP in south Delta Mahakam area. The result of analysis showed environmenal sensitivity was 62.37% (517.52 km), its mean very high sensitivity. Then the high sensitivity criteria was 11.31% (94 km). The criteria of medium sensitivity was 11.92% (99 km). While for low sensitivity and very low sensitivity respectively were 1.78% (15 km) and 12.64% (105 km). Based on Principal Component Analysis (PCA), 36.01% variability was explained by axis of factor 1. The others variability 18.53% and 13.93% were explained by axis of the factor 2 and factor 3. Axis of factor 1 for coastal exposure (EK), oil residence index (OR), coastal type (TP), and biological resources (SH) had a quite large linear combinations coefficient, amounted to 0.94 (EK&OR), 0.83 (TP) and 0.75 (SH). This indicated a very high contribution for environmental sensitivity OSCP level drafting. On axis of factor 2, the linear coeffisien combinations for the resource utilization of port (PL) was 0.83 and settlement (PM) was 0.85. Axis of factor 3 contributed 0.75 and 0.66 on migas platform (PO) and placement of passive fishing gear/catchment area (AT). However, the utilization of coastal resources for PL, PM, PO and AT were on axis of factor 2 and factor 3 had a considerable distance with its SI variable. This possible caused by each variable percentage distribution which the value was very minor ranged 0.001-0.52%, so its not representated coastal resources elements closeness with SI variable in the study area.Keywords: Environmental Sensitivity, Oil Spill Contingency Plan, Mahakam Delta